Youth, Electoral Violence, and Political Power in Kaduna State, Nigeria: Ethno-Political Mobilization and Democratic Stability in West Africa - Yusuf Bala; Mohd Mahadee Ismail (Goodwood Publishing, 2026)
Purpose: Electoral violence remains a major challenge to democratic governance and youth socioeconomic development in Nigeria, particularly in Kaduna State. This study examines the relationship between youth political inclusion, electoral violence, and future prospects within the broader context of democratic stability in West Africa. Methodology: A quantitative research design was applied using survey data from 200 respondents during the 2023 general election in Kaduna State. Data were analyzed using descriptive statistics, Pearson correlation, and multiple regression to examine the political and structural factors influencing youth involvement in electoral violence. Results: The findings show that the youth occupy dual roles as perpetrators and victims of electoral violence, driven by political elite manipulation and structural inequalities. Unemployment, poverty, and political exclusion increase the youth’s vulnerability to violence. Electoral violence negatively affects youth future prospects (r = −0.604, p < 0.01), whereas political inclusion positively influences future prospects (β = 0.361, p < 0.001), highlighting the broader socio-political and economic inequalities undermining youth development. Conclusions: The study concludes that promoting inclusive political participation, expanding economic opportunities, and strengthening democratic institutions are critical for reducing electoral violence and improving youth future prospects. Limitations: As the research relied on cross-sectional survey data from selected areas of Kaduna State, the findings may not fully capture long-term changes over time. Contributions: This study contributes to the existing literature by demonstrating the interconnectedness of electoral violence, political inclusion, and youth future prospects, while providing policy directions for democratic consolidation and sustainable peace in Nigeria and West Africa.